2017
DOI: 10.4049/jimmunol.1602042
|View full text |Cite
|
Sign up to set email alerts
|

Activated B Cells Participating in the Anti-Myelin Response Are Excluded from the Inflamed Central Nervous System in a Model of Autoimmunity that Allows for B Cell Recognition of Autoantigen

Abstract: Once activated, T cells gain the ability to access both healthy and inflamed nonlymphoid tissues. They are then reactivated to remain in the tissue and exert their effector function only if they encounter their specific Ag. In this study, we set out to determine if the same is true for B cells using a mouse model of CNS autoimmunity that incorporates both T and B cell recognition of a myelin autoantigen. Both T and B cells were common infiltrates of spinal cords in diseased mice. However, unlike T cells, anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Further, subcutaneous immunization with MOG protein is a well-established method to induce the anti-myelin autoimmune model experimental autoimmune encephalomyelitis (EAE). In our hands, mice immunized with mMOG tag develop a robust disease with evidence that GC-derived anti-MOG B cells contribute to both disease severity and chronic disease course (Dang et al, 2015; Tesfagiorgis et al, 2017). Therefore, although short-lived, the MOG GC is productive.…”
Section: Discussionmentioning
confidence: 84%
“…Further, subcutaneous immunization with MOG protein is a well-established method to induce the anti-myelin autoimmune model experimental autoimmune encephalomyelitis (EAE). In our hands, mice immunized with mMOG tag develop a robust disease with evidence that GC-derived anti-MOG B cells contribute to both disease severity and chronic disease course (Dang et al, 2015; Tesfagiorgis et al, 2017). Therefore, although short-lived, the MOG GC is productive.…”
Section: Discussionmentioning
confidence: 84%
“…Exclusion of B cells from the CNS results in reduced severity of EAE induced by rhMOG yet exacerbates EAE induced by MOG 35-55 peptide, indicating that access to the CNS is required for EAE mediated by B cell antigen presentation yet can also be important for regulatory B cells to ameliorate disease [ 49 51 ]. In contrast, Tesfagiorgis et al found that antigen-nonspecific B cells are recruited to the CNS compartment while myelin-specific B cells remain in the peripheral draining lymph nodes in a model of active EAE that requires B cells [ 52 ]. In our model, the relative infrequency of B cells observed in the CNS of mice that develop EAE may reflect the ease with which MOG-specific B cells capture their soluble protein antigens to present to T cells within the CNS compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The blood, lymph nodes (inguinal, axillary, and cervical), spleen and the spinal cord were harvested from mice for flow cytometry analysis as previously described (18, 33). Briefly, blood was isolated through a cardiac puncture with needles pre-washed with 0.5M EDTA, after which the mouse was perfused with ice cold PBS prior to harvesting other tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The blood, lymph nodes (inguinal, axillary, and cervical), spleen and the spinal cord were harvested from mice for flow cytometry analysis as previously described (18,33…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation